Severe conditioned zinc deficiency in breast-fed premature infants. - Ottevanger, V.; Hansen, E.R.; Petersen, C.S.; Weismann, K. (European Journal of Pediatric Dermatology, 2018)
We report three similar cases of acquired zinc deficiency in preterm breast-fed male infants, associated with, in two of the cases, a low zinc content in their mothers breastmilk. The infants were initially misdiagnosed as having eczema with superinfection. The skin signs disappeared promptly with oral zinc therapy and the patients' serum zinc levels normalized.